The Physical Learning Environment as a Stimulus for Children’s Critical Thinking: A Systematic Review - Handoko, Herdi; Lathifah, Inayatul; Dian Pertiwi, Adharina; Kurnia, Devi; Wahyu Chandra Utami, Laksmita; Idmi Martuji, ⁠Sazliana; Hayati, Nur (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2025)
The physical learning environment in early childhood education plays a central role in shaping children’s learning experiences, social interactions, and cognitive development. Grounded in the Reggio Emilia concept of the environment as the “third teacher,” this article presents a systematic review of empirical studies examining how physical learning environments support the development of critical thinking and problem-solving skills in early childhood. Using the PRISMA-guided Systematic Literature Review approach, 223 initial records published between 2015 and 2025 were screened, resulting in 20 empirical studies that met inclusion criteria, consisting of 15 empirical articles and 5 essential theoretical or methodological articles. Thematic synthesis generated four major themes: spatial organization that promotes autonomy and collaboration; open-ended materials that stimulate exploration and representational thinking; indoor–outdoor continuity that provides authentic reasoning contexts; and teacher mediation that transforms environmental affordances into meaningful cognitive engagement. Findings indicate that well-designed learning environments that are comfortable, aesthetically rich, and creatively arranged enhance children’s motivation, inquiry behaviors, reasoning skills, and ability to solve problems. This review highlights practical implications for teachers, curriculum designers, and school administrators in optimizing the learning environment to foster higher-order thinking in early childhood education